VO₂max as a Vaccination Against Lifestyle Diseases – Impact on Longevity, Disease Incidence, and a Marker of Fitness - Szaryński, Mikołaj; Jakubowska, Paulina; Lewandowska-Mackiewicz, Aleksandra; Poręba, Martyna; Jakubowska, Martyna; Peszt, Michał Józef; Poręba, Kacper; Prokopczyk, Kamila; Wasilczuk, Antoni; Matuszewska, Julia; Rusiłowicz, Rafał (Quality in Sport, 2025)
Cardiorespiratory fitness, assessed by maximal oxygen uptake (VO₂max), is a powerful marker of health and longevity. This review summarizes epidemiological and clinical evidence demonstrating that higher VO₂max reduces the risk of lifestyle-related diseases, including cardiovascular disease, type 2 diabetes, cancer, chronic inflammation, and multimorbidity in older adults. Analysis of studies indexed in PubMed, JACC, OUP, ScienceDirect, and PMC shows that low VO₂max is strongly associated with increased all-cause and cardiovascular mortality, whereas even modest improvements in VO₂max significantly lower mortality risk. VO₂max reflects the integrated function of respiratory, cardiovascular, and muscular systems and serves as an independent predictor of long-term health outcomes. Regular physical activity, particularly high-intensity interval training (HIIT), but also moderate intensity aerobic exercise effectively increases VO₂max through central and peripheral adaptations, improving cardiac output, muscle perfusion, and mitochondrial function. These adaptations reduce chronic low-grade inflammation, enhance insulin sensitivity, and improve metabolic and cardiovascular profiles. Due to its protective effects, high VO₂max could be described as a “vaccination against lifestyle diseases.” Evidence indicates that maintaining VO₂max above threshold values markedly improves survival and should be considered a key component of preventive health strategies. VO₂max thus represents a critical public health indicator deserving integration into routine clinical practice.